Factors associated with oropharyngeal dysphagia in individuals with cardiovascular disease and COVID-19 - de Almeida, Tatiana Magalhães; Fernandes, Raquel Gama; Binhardi, Vitor Della Rovere; França, João Italo Dias; Magnoni, Daniel; da Silva, Roberta Gonçalves [UNESP] (FapUNIFESP (SciELO), 2024)
Purpose: Oropharyngeal dysphagia (OD) is one of the possible outcomes in patients hospitalized with COVID-19 and also in the population hospitalized for the treatment of cardiovascular disease. Thus, knowing the predictive risk factors for OD may help with referral and early intervention. This study aimed to verify the association of different factors with OD in hospitalized individuals with cardiovascular disease and COVID-19. Methods: Cross-sectional clinical study approved by the Research Ethics Committee (4, 521, 771). Clinical evaluation of swallowing was carried out in 72 adult patients with cardiovascular disease and COVID-19 hospitalized from April to September 2020. Individuals under 18 years of age and without previous cardiovascular disease were excluded. The presence of general clinical and/or neurological complications, pronation, stay in the intensive care unit (ICU), orotracheal intubation (OTI), tracheostomy tube, oxygen support and age were considered as predictive risk factors for oropharyngeal dysphagia. Fisher’s exact test, Mann Whitney test and logistic regression model were used for analysis. Results: General clinical complications (p=0.001), pronation (p=0.003), ICU stay (p=0.043), in addition to the need for oxygen supplementation (p=0.023) and age (p= 0.037) were statistically significant factors associated. The pronation (0.013) and age (0.038) were independently associated with dysphagia. OTI (p=0.208), tracheostomy (p=0.707) and the presence of previous cerebrovascular accidents (p=0.493) were not statistically significant. Conclusion: In this study, age and prone position were factors independently associated with oropharyngeal dysphagia, complications such as the need for oxygen supplementation, in addition to the need for ICU admission, were also associated factors in the population.
Keywords: Aging; Cardiovascular Diseases; Coronavirus Infections; Intratracheal Intubation; Swallowing Disorders